Quranic Parenting; a Study of Maryam's Upbringing Story from Surah Ali Imran: 33-37 - Ramli, A.; Ali, N. B.; Ahmad, H. (Universiti Sains Islam Malaysia, 2024)
As children are the future of mankind, bringing them up refers to the preparation of civilization. The most important environment to ensure their proper growth is a family. Getting a proper and well-structured nurturing is one of their rights which should be ensured by the family. The unwillingness to refer to the Quran caused many families unaware that the Quran provides best method of nurturing and upbringing children. One of the samples is the role of Imran's Family in nurturing their child named Maryam as she possesses a decent personality and become an honorable woman. This paper is trying to analyze an upbringing concept explained in Surah Ali Imran (33-37), that may be applied today. This study also presents that the Quran has a golden nurturing concept in upbringing children, and the children who have received their rights well fulfilled will become an excellent person, individually and spiritually.